Healthy lifestyle behaviors among teachers working in public primary schools and affecting factors - Örs, Mukaddes (Frontiers in Public Health, 2024)
Healthy lifestyle behaviors have been recognized as a key strategy to achieve a policy of health for all. The aim of this study was to determine the levels of health promotion lifestyle behavior among teachers working in public primary schools. The present study also investigated the effects of selected socio-demographic characteristics on these behaviors. The research was designed using the survey model, one of the quantitative research methods. The sample of the research consisted of public primary school teachers (n = 372). Research data were collected using the Health-Promotion Lifestyle Profile-II (HPLP-II) scale. As a result of the research, it was put forward that there were statistically significant differences in levels of health promotion lifestyle behaviors based on taking courses on health promotion, and following programs and articles about healthy living (p < 0.05). It was revealed that primary teachers' taking courses on health promotion, and following programs and articles affected their healthy lifestyle behaviors. Public primary school teachers' health promotion lifestyle behaviors were found to be moderate. It was found that the primary teachers obtained the highest mean score for the spiritual growth subscale of the health promotion lifestyle behaviors scale; however, the primary school teachers had the lowest mean score for the physical activity subscale, which indicates that they need support in improving their healthy lifestyle. Male teachers had higher mean scores in the physical activity subscale, whereas females had higher mean scores in all other subscales. Training programs to protect and improve the health of teachers should be organized.